The Effectiveness Growth of Males and Females Crabs (Scylla Serrata) In Recirculation System - Yudha Lestira Dhewantara; Firsty Rahmatia; Reyhan Salindro Usman (Airlangga University, 2021)
Crab (Scylla serrata) is a commodity that has high prospects for cultivation. Cultivation in Indonesia has not been intensive and densely spread low due to the threat of crab deaths due to cannibalism. The purpose of this study was to determine the comparison of the growth of male and female crabs in the recirculation system to increase the productivity of mangrove crab. The research was conducted from November 2019 to June 2020 at the Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences Satya Negara University of Indonesia and blood tests were conducted at the Center for Freshwater Aquaculture Fisheries- Bogor. The experiment used a Complete Randomized Design (CRD) consisting of three treatments and five replicate each. The treatments consisted of: A: male crab; B: female crab; C: Control. The number of seeds that used in this study were 5 for each treatment with five replications and density of 5 crab per maintenance container (gallon). The feed provided were fish feed selar Atule mate which was cut into small pieces. The selar fish came from Muara Angke, North Jakarta. Feeds were given with frequency 4 times a day. The results showed that the growth of male and female mangrove crab gave the best production performance in the treatment of female maintenance containers with survival rate of 53.33%, absolute growth rate of 3.76 g, and carapac width of 3.44 mm.Keywords: crab (Scylla serrata.), growth, recirculation system